A atuação do psicólogo no ensino público do Paraná : contribuições da psicologia hitórico-cultural - Lessa, Patrícia Vaz de (2010)
Various studies have been currently carried out to analyze the practices of school psychologists, who have to deal with school-related complaints. This study aims to contribute with this investigation and its general objectives are to identify and analyze the practices developed by psychologists in the public schools of Paraná State as well as to examine how such complaints are dealt with, within the investigated group. It also looks at understanding how the professionals present elements of critical concepts in their performance, relevant to the recent discussions in the field of School and Educational Psychology that allows everyone access to historically produced knowledge. The study sought reasons in the assumptions of the Cultural-historical psychology - that sits on the historical-dialectal materialism; on literature review which draws a profile of the historical movement that constitutes psychology as an area of knowledge in Education; and finally on field research carried out with psychologists. It has briefly discussed the historical constitution of the school psychologist, initially supported by a traditional point of view, criticized in the 1980´s, resulting in a performance based on assumptions of the Cultural-Historical Psychology, grounded on Marxism. As for the field research carried out among the psychologists, in the first phase, out of 385 questionnaires sent, 85 were answered. In the second phase, nine professionals were selected from the interviews. These professionals demonstrated elements in their answers that make up a critical conception of their practice. Then, the data collected from the questionnaire will be presented. Among the most important results, the fact that professionals go through a transitional period has been emphasized, for it has been noticed throughout the research that there is an ongoing movement towards practices and understanding of school complaints pointed out in the actions that involve the school context, which seeks to outgrow the traditional view, with a clinical focus. We consider that this work can be justified by the contributions and reflections as to the usage of the assumptions of Vygotsky school to the dialectal understanding the involves human relationships in the school context. It is also considered that this research may contribute by approaching Psychology as a means to map the presence of psychologists in the public schools of Paraná State. Analysis based on these theoretical groundings may contribute to the interpretation of school reality and interventions that take into account the historical background existing in the pedagogical process. The reflection on how we use our knowledge and understanding of such processes must be constant and continual in our practices and must contribute to the process of socialization of scientific knowledge.